Efektivitas Penggunaan Lembar Kerja Peserta Didik (LKPD) Berbasis Model Project Based Learning Berbantuan Aplikasi Tracker dengan Pendekatan Saintifik pada Materi Kinematika Gerak - Lismidarni, Susri (Universitas Negeri Padang, 2020)
This reseach is motivated by physics learning that has not been running according to the curriculum 2013 reference. The curriculum 2013 was develop based on two factors, one of which is external challenges including environment issuess, advancement ofÂ information technology, the rise of creative and cultural industries and development of education at the international level. An innovation is needed in the form of developing models, sources and learning media that are in line with the demands of the currculum 2013 as one simple learning resource that easily understood by student. The project based learning model as one model of the models recommended in the curriculum 2013 because it can improve student competence and creativity as well as the tracker application as an IT based learning media that can complete atÂ Internatinal levels. The purpose in study was produce project based learning assisted tracker application with scientific approuch on the topic of kinematics for 10th grade senior high school with effective criteria. The LKPD that was developed was effective in improving students' competencies including knowledge competencies (82,57), attitude competence (81,9), skills competence (81,8). Based on the results of the study it can be produce project based learning assisted tracker application with scientific approuch on the Topic of Kinematics For 10th Grade Senior High School with effective criteria